Preparation Methods of μg Carbon Samples for 14C MeasuremenTS. Issue 3 (14th December 2016) - Steier, Peter; Liebl, Jakob; Kutschera, Walter; Wild, Eva Maria; Golser, Robin
Abstract: Systematic investigations and experience from several application projects on small carbon samples over a number of years have resulted in measuring the radiocarbon content of 10 μg C samples with an overall precision of typically 1%. A substantial reduction of the carbon contamination during graphitization was achieved, resulting in 31±30 ng modern and <100 ng 14 C-free carbon. Thus, graphitization is no longer the limiting factor because earlier sample preparation steps usually introduce much larger contamination. The method has been extended to a variety of materials and applied to various projects. Realistic conditions for procedure development can only be achieved in the context of applications on true samples; methods developed are the lyophilization of samples in solution, combustion, ultraviolet oxidation, or carbonate hydrolysis with phosphoric acid, which allows to prepare samples for a wide range of applications. Insights gained from systematic investigations and from real applications are presented.